1997
DOI: 10.1086/310685
|View full text |Cite
|
Sign up to set email alerts
|

On a Rapid Lithium Enrichment and Depletion of K Giant Stars

Abstract: A model scenario has recently been introduced to explain the presence of very strong Li lines in the spectra of some low mass K giant stars (de la Reza et al. 1996). In this scenario all ordinary, Li poor, K giants become Li rich during a short time ($\sim 10^5 yr$) when compared to the red giant phase of 5 10^7 yr. In this ``Li period'', a large part of the stars are associated with an expanding thin circumstellar shell supposedly triggered by an abrupt internal mixing mechanism resulting in a surface new ^7L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 17 publications
(20 reference statements)
6
98
2
Order By: Relevance
“…In agreement with this, Kraft et al (1999) De la Reza et al (1996Reza et al ( , 1997 proposed a different scenario for the Li production along the RGB, associated with short episodes of mass loss occurring just after each extra-mixing event. In this way, some fresh Li would be produced when convection penetrates close to the H-burning shell, which might occur at the RGB bump or brighter.…”
Section: Circumstellar Materials and Infrared Excessmentioning
confidence: 82%
See 1 more Smart Citation
“…In agreement with this, Kraft et al (1999) De la Reza et al (1996Reza et al ( , 1997 proposed a different scenario for the Li production along the RGB, associated with short episodes of mass loss occurring just after each extra-mixing event. In this way, some fresh Li would be produced when convection penetrates close to the H-burning shell, which might occur at the RGB bump or brighter.…”
Section: Circumstellar Materials and Infrared Excessmentioning
confidence: 82%
“…The thin layer containing fresh Li would be quickly carried to the surface (and observed) but would be lost by the star immediately afterwards. Observational support of this scenario was given by the detection of infrared excess in some Li-rich giant stars (Gregorio-Hetem et al 1993;De la Reza et al 1996, 1997Castilho et al 1998).…”
Section: Circumstellar Materials and Infrared Excessmentioning
confidence: 93%
“…Exploring the RGB hypothesis further, de la Reza et al (1997) argue that, at a certain point in the life of a giant, an abrupt mixing mechanism can lead to a rapid surface injection of material with fresh internal 7 Be, which is rapidly transformed to 7 Li. The same mechanism would then enable the formation of a circumstellar shell of gas and dust that is later ejected in the interstellar medium.…”
Section: Discussionmentioning
confidence: 99%
“…when the stars evolve out of the main sequence; but this scenario should suggest that lithium-rich K-giants may have spotted lithium-rich Ap progenitors, a new scenario that needs more detailed analysis in the future. The discovery of this large number of lithium-rich giants adds more than 40% to the known ones (40 quoted by de la Reza et al 1997b; 15 quoted by Pereyra et al 2006, and some other dispersed in the literature). Our results reinforce those of Fekel & Balachandran (1994), who found that 58% of single active giants have high lithium abundance (36% for the giants in binary systems) and are also in line with a 50% of lithium-rich stars among rapidly-rotating K-giants found by Drake et al (2002).…”
Section: Lithium-rich Giantsmentioning
confidence: 92%